‘Grammars of displacement’: Kojo Laing’s lines of flight - Hankinson, J (Taylor & Francis, 2024)
Departing from the relationship between the texts of the Ghanaian poet and novelist Kojo Laing and a recent international art exhibition, this article traces the relationship between style and the multivalent activity of flight across Laing’s work. Drawing upon an intercontinental range of philosophers – from Deleuze and Guattari to contemporary Akan thinkers – it analyses the intersections between gender, geography, and language in Laing’s texts, and demonstrates their value within the context of discussion of contemporary literature’s investment in possible futures. Laing’s transnational aesthetic foregrounds lines of flight across and between different linguistic and cultural communities, and traces relentlessly emerging or possible constellations of relation. Situating Laing in the context of his interdisciplinary reception, this article seeks to explore the aesthetic and ethical ramifications of the unusual networks of affiliation and response of one of West Africa’s most important, yet critically undervalued, contemporary writers.